A study on factors influencing turnover intention among employees in Klana Beach Resort Port Dickson / Siti Naquiah Amizee - Amizee, Siti Naquiah (2014)
Employee turnover is one of major problem facing by organization nowadays. Employee turnover makes the organization to face with losses such as high expenses and slow productivity. There are several consequences of turnover. Those negative impacts are high financial cost, workflow interruptions, loss of expertise, loss of business opportunities and administrative problems. The higher level of turnover in the organization will cause the problem that will impact the employee retention and production. The purpose of this study is to identify the factors that influence turnover intention among employees. The objective of this study is to identify the relationship between compensation, working environment and supervisory support towards turnover intention among employees. The data has been collected from employees in KBRPD. The total number of respondents is 35 people selected through convenient sampling. Questionnaire is distributed to collect all the data and is interpreted into readable and informative data through reliability analysis, descriptive analysis and Pearson’s correlation. After the data has been analysed, the result showed that there is a significant correlation relationship between compensation, working environment and supervisory support towards turnover intention. At the end of this research, some recommendation also been discussed.